Contribuição para uma crítica ontológica à ideologia de Hannah Arendt: natalidade, história e revolução - Sartori, Vitor Bartoletti (2011)
The objective of this writing is to make explicit the essential determinations of Arendt´s thought, that cannot be seen only with Lukács, concept of irrationalism, but are inseparable from it. Arendt´s ideology is developed during the Weimar republic and, after de second world war, on the USA and has strong relations with her project regarding the totalitarian elements of Marxism . Can be considered part of this project the books Between Past and Future, The Human Condition and On Revolution. Taking in account Hannah Arendt´s position towards reality, we intend to show the origins of Arendt s thought on her telos opposite to Marxism, socialism and, mainly, to the conscious control of the economy. The concrete position of the author, as a result, we intend to prove, is related at the same time with the German irrationalism and with the liberal-conservative tradition expressed in Toqueville and Burke mainly. So, finally, we analyze how she is next to religious atheism (analyzed by Lukács) when it comes to comprehend the arendtian narrative on the American and on the French Revolution. Both narratives are essential when we take on account that the author is opposed not only to the French revolution, but also to socialism, the Russian Revolution, and humam emancipation